Markers of endometrial biological fluids in the diagnosis of uterine adnexal tumors - E. G. Shvaryov; L. V. Dikaryova; D. L. Ovodenko; A. K. Ayupova; G. E. Shvaryov (Опухоли женской репродуктивной системы)
As it is known, the problem of intensification and optimization of pre-hospital diagnostics largely determines the success of treatment and is one of its most important items. It is this approach that gives an opportunity for effective, preserving organs, treatment and thus at most saves reproductive abilities of women. Nowadays the problem of screening precancerous and cancerous diseases of uterine body and appendages, which are increasing in population, is still unsolved. It is the necessity of regular prophylactic measures, in the aspect of forming the considered diseases, that consists in high chances of their elimination just when they are early revealed. The object of research is clinico-laboratory data of 176 patients consisted of 45 (25.6 %) women control group without tumors of reproductive organs, all the rest were divided into two groups: the first one consisted of 87 (49.4 %) patients with ovarian tumors (benignant and malignant) and the second group included 44 (25.0 %) patients with adnexitis.Objective: to improve the diagnostics of the adnexis tumors by indentification structural and biochemical markers in menstrual discharges and endometrial washes. The study used сlinical, pathohystological, cytological, biochemical, statistical methods and the methods wedge-shaped dehydration of biological liquids, transvaginal echography.